Conciencia ambiental y su relación con el cuidado del ambiente en estudiantes del quinto nivel secundario de la Institución Educativa Santa María del Amazonas. Tamshiyacu. 2021 - Montoya Pizango, Anais Azucena (2022)
The present investigation seeks to understand the relationship of environmental awareness with the care of the environment in students of the 5th secondary level of the I.E. Santa Maria del Amazonas, Tamshiyacu. The research is non-experimental, quantitative, cross-sectional, descriptive level, with a simple probabilistic sample of 45 students. Perception was evaluated under the affective, cognitive, conative, and active dimensions. The results allow to understand that the students show a good level of knowledge in relation to the care of the environment, thus all refer that environmental education is important for the improvement of environmental awareness and likewise the majority (55.6%) warn of environmental problems in your city, such as gases, river pollution, etc.; there are institutions that are concerned about environmental protection, such as the municipality and its Environmental Area (75.5%), the majority (73.3) affirm that the contamination is due to man and consider that due to some environmental problems it is not possible to live well (48.9 %). In the affective, almost all students (93.3%) appreciate the defense of the environment and do not accept anthropic activities that disturb the environment (100%), and lifestyles should be changed to keep nature in balance (100%), In another aspect, a high percentage (88.9%) report that animals are similar in feeling to humans and all environmental problems must be taken into account. In the conative, all the students are willing to act in the recycling of waste, willingness to take care of water, they internalize actions to avoid environmental threats in which the vast majority (86.7%) show willingness to participate in volunteering. Behaviorally, a high percentage of students (77.8%) say they want to avoid polluting the environment, all say they save electricity and water, recycling practices and their participation in pro-environmental organizations; Thus, regarding care for the environment, the vast majority (82.2%) say that they dispose of plastic waste in containers, 55.6% refer to exhibiting their work at environmental fairs.